1991
DOI: 10.2307/1966778
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Contraception, and Pregnancy Among Adolescents in Mexico City

Abstract: This article presents the development and results of a study that analyzed the psychosocial determinants of abstaining from sexual intercourse, practicing contraception, and avoiding pregnancy. It was carried out with a representative household and a clinic sample of 12-19-year-old females of lower-middle and lower socioeconomic levels in Mexico City. Among the implications of the results for program design are: (1) the need for clarifying erroneous beliefs and providing detailed, practical knowledge concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 9 publications
1
7
0
3
Order By: Relevance
“…The study of male adolescents in Lima, described in the introduction, found that participants who had repeated a grade were more likely to be sexually active than those who had not repeated a grade (Chirinos et al, 2000). Two other studies in Latin America, one with female adolescents in Mexico City and one with female and male adolescents in Ecuador, showed that respondents with higher educational aspirations were less likely to have had sex (Park, Sneed, Morisky, Alvear, & Hearst, 2002; Pick de Weiss, Atkin, Gribble, & Andrade-Palos, 1991). Adolescent participants in this study individually rated being a good student and meeting future goals and objectives as highly important to their sexuality, but during the role plays and related discussions, they highlighted the complexities related to future aspirations in the current context.…”
Section: Discussionmentioning
confidence: 96%
“…The study of male adolescents in Lima, described in the introduction, found that participants who had repeated a grade were more likely to be sexually active than those who had not repeated a grade (Chirinos et al, 2000). Two other studies in Latin America, one with female adolescents in Mexico City and one with female and male adolescents in Ecuador, showed that respondents with higher educational aspirations were less likely to have had sex (Park, Sneed, Morisky, Alvear, & Hearst, 2002; Pick de Weiss, Atkin, Gribble, & Andrade-Palos, 1991). Adolescent participants in this study individually rated being a good student and meeting future goals and objectives as highly important to their sexuality, but during the role plays and related discussions, they highlighted the complexities related to future aspirations in the current context.…”
Section: Discussionmentioning
confidence: 96%
“…This categorization is based on existing literature (e.g. De Weiss et al 1991;Barker and Rich 1992) which has mainly emphasized the distinctive role of peers and parents in the adolescent socialization process. In this model, we consider the index of gender-role attitudes as the covariate of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents have still largely been approached as a high risk group because of their engagement in sexual behavior while lacking in maturity, forethought, skills, and experience (Pedlow & Carey, 2004;Persson, 1993;Rosenthal, Smith, & De Visser, 1999;Scott, Reppucci, & Woollard, 1995). Adolescent behavior has been largely viewed through the lens of the HIV/AIDS and STDs (Brooks-Gunn & Furstenberg, 1990;DiClemente, 1993;Gagnon, 1988;Weiss, Whelan, & Gupta, 1996), unwanted pregnancies and abortions (Jones, 1986;Pick de Weiss, Atkin, Gribble, & Andrade-Palos, 1991;Saito, 1998), and problem behaviors (Epstein & Tamir, 1984;Jessor & Jessor, 1977;.…”
Section: Introductionmentioning
confidence: 99%